(untitled) (Papeles, 2026)
Introduction: The teaching of mathematics to deaf students faces challenges due to the absence of standardized technical terminology in Mexican Sign Language (LSM). This gap creates terminological voids that limit equitable access to mathematical knowledge. Teachers often rely on iconic representations, visual analogies, or the fingerspelling of technical terms; however, these alternatives are insufficient, as they transmit information but do not always ensure full conceptual understanding. In this context, the creation of new signs emerges as a way to overcome such limitations, although in Mexico this practice has been scarcely documented. Methodology: The aim of this study was to analyze the creation of signs carried out by a deaf teacher to explain mathematical concepts without an equivalent in LSM. A qualitative approach was adopted through a case study, combining participant observation and a semi-structured interview, with the mediation of an LSM interpreter. The analysis was organized into three categories: terminological gaps, strategies for sign creation, and validation in the classroom. Results: The findings show that there are no specific signs for elementary algebra concepts, which motivates the development of new proposals through non-systematic steps and in interaction with the community. Validation depends mainly on their acceptance in school practice and in spaces of socialization within the deaf community, rather than on external regulatory processes. Conclusions: The creation of signs represents a pedagogical strategy to address the challenge of teaching mathematical technical terms to deaf students, as it promotes both communication and conceptual understanding.